SAT0361 HEALTHY HUMAN SPINAL PROCESSES PERI-ENTHESEAL T-CELLS EXHIBIT A TR1 RATHER THAN A FOXP3 REGULATORY PHENOTYPE. (13th June 2020) - Rowe, H.; Watad, A.; Russell, T.; Sharif, K.; Newton, D.; Wittmann, M.; Zhou, Q.; Khan, A.; Loughenbury, P.; Dunsmuir, R.; Rao, A. S.; Millner, P.; et al.
Abstract : Background: We have previously reported that the normal spinal enthesis has populations of conventional T-cells including CD4+ & CD8+ T-cells that could be induced to produce IL-17A and TNF following anti-CD3/CD28 stimulation. The biology of such cells in health including their normal function and antigen reactivity is completely unknown. The purpose of this work was to define the phenotype, functionality and TCR reactivity of such T-cells in health. Objectives: To investigate whether the T-cells at the normal enthesis were regulatory in nature and to determine the type of regulatory T-cell as Tr1 or FOXP3 regulatory T-cell and to determine T-cell reactivity. Methods: Healthy interspinous ligament and spinous process with matched peripheral blood were harvested from patients undergoing elective spinal surgery (n=20). Entheseal soft tissue (EST) & peri-entheseal bone (PEB) was enzymatically digested and then sorted. Tr1 and Treg phenotypes were investigated using flow cytometry. Analysis of cytokines, growth factors and chemokines was performed by qRT-PCR, ELISA and flow cytometry. TCR sequencing was performed and a search for putative T-cell reactivity was done using TCR3 database. Results: Pro-inflammatory cytokine transcripts including IL-17A, IL-17F, IL-22, IL-23 (p19) & TNF were very low or undetectable in the Enthesis T-cells (Fig 1). Flow cytometry confirmed entheseal T-cells had a Tr1 phenotype (CD4+ LAG3+ CD49b+). Intracellular flow cytometry showed enthesis T-cells had very low FOXP3 expression, when compared to their blood counterparts. Intracellular flow cytometry and gene expression showed high basal expression of growth factors and regulatory proteins such as IL-10 & TGFβ, when compared to blood T-cells. RNA-Seq data, showed 13 potential TCR clonal sequences the most common of which are predicted to be reactive viral infection was CMV present in 8 sequences and Influenza A virus present in 2 sequences. Conclusion: The healthy human enthesis has regulatory T-cells of a Tr1 phenotype rather than a FOXP3 Treg phenotype. Many clones have antigen specificity indicating reactivity to prior infection. These findings suggest that conventional entheseal T-cells have a role in enthesis immune homeostasis. Disclosure of Interests: Hannah Rowe Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Abdulla Watad: None declared, Tobias Russell Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Kassem Sharif: None declared, Darren Newton: None declared, Miriam Wittmann: None declared, Qiao Zhou Grant/research support from: Funded by the PARTNER fellowship program, Almas Khan: None declared, Peter Loughenbury: None declared, Robert Dunsmuir: None declared, Abhay S Rao: None declared, Peter Millner: None declared, Tony Kenna: None declared, Matthew Brown: None declared, Charlie Bridgewood: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC